Some problems concerning conceptualization of the world by means of natural language - Aleksandr P. Zhuravlyov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with some problems concerning conceptualization of the world by means of natural language. The article analyzes the role of conceptualization in the process of experiencing and describing the world, as well as the way the individual cognitive features of a person influence the conceptualization of objects and how these concepts are represented by means of natural language. These problems are partially caused by unclear definition of concept given in scientific works of various researchers; furthermore, different branches of cognitive sciences connected with cognitive linguistics provide different meanings of the term “concept”. Other reason is linguocultural features of people speaking different languages.